THE ANALYSIS OF INSTITUTIONAL PROFILE AT THE MIFTAHUL KHOIR UNIVERSITY STUDENT ISLAMIC BOARDING SCHOOL, BANDUNG IN IMPLEMENTING ISLAMIC EDUCATION - Hidayat, Tatang (Program Studi Pendidikan Agama Islam, 2018)
This study aims at investigating the institutional profile at the Miftahul Khoir University Student Islamic Boarding School, Bandung in implementing Islamic education. This study employed a qualitative approach and descriptive method. In this study, the researchers acted as the instrument. The techniques of collecting the data were carried out through interviews, observation, and documentation studies. Then, the techniques of analyzing the data covered data reduction, data display, coding, and drawing conclusions. In order to test the validity of the data, the researchers conducted a credibility test by conducting research persistence, triangulation, adding references, and member check. Based on the results of the study, the vision, mission and objectives of Islamic education in this Islamic boarding school are to integrate the life of the world and the hereafter. The education curriculum in this Islamic boarding school consists of the syllabus programs and non-syllabus programs. In addition, the teachers also have different scientific chain of narration or sanad, the majority of students are university students, and the education staff consists of the boarding school administrators and students or santri. In relation to the infrastructure, it is quite complete and the education evaluation is also quite comprehensive. The Miftahul Khoir University Student Islamic Boarding School, Bandung is considered as a boarding school that is capable of carrying out Islamic education because it is equipped with the adequate educational components.